The Effect of Play Therapy on Social Interaction of Learners with Autism Spectrum Disorder: A Literature Study - Ulyanisa Adibah, Ghita Maulida; Yusup, Febrianawati (Pedagogi: Jurnal Ilmu Pendidikan, 2025)
Learners with Autism Spectrum Disorder (ASD) often experience barriers in establishing social interactions that have a direct impact on relational development at school. Play therapy is one intervention approach that is considered effective in stimulating social development through fun and structured activities. This study aims to examine the effect of play therapy on the social interaction of learners with ASD through a literature study. Twenty articles published in the last five years were analyzed, selected based on criteria of thematic relevance. The review categorized play therapy into five approaches, including direct social, music and movement, visual and manipulative, collaborative play, and physical intervention. The review found that all of these approaches can improve social dimensions such as eye contact, reciprocal communication, cooperation and emotional expression. The conclusion of this study suggests that play therapy should be integrated into inclusive education practices as part of social interventions for learners with ASD.